2021
DOI: 10.4103/hm.hm_25_21
|View full text |Cite
|
Sign up to set email alerts
|

Low-carbohydrate Diet Improves the Cardiopsychiatry Profile of Patients with Schizophrenia

Abstract: Background and Objective: Patients with schizophrenia are more prone to develop metabolic syndrome (MetS) with its related complications, including cardiovascular diseases and diabetes mellitus compared to the general population. In this study, we aim to evaluate the effect of low-carbohydrate diet on MetS Z score, weight status, and symptomatology of patients with schizophrenia in Bahrain. Materials and Methods: This single-group pretest–posttest study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…We also showed that exercise combined with KD significantly improved the Zmets compared with exercise alone. In line with our results, previous studies have shown that low-carbohydrate diet (48) and physical activity (49) interventions improve the most prevalent MetS components, especially MetS Z-score (Zmets). Because the measures of interaction on the additive scale revealed that the combined effects of exercise and KD on Zmets were more than the sum of the individual effects, current results support their synergistic effect and importance for the control of MetS conditions.…”
Section: Discussionsupporting
confidence: 92%
“…We also showed that exercise combined with KD significantly improved the Zmets compared with exercise alone. In line with our results, previous studies have shown that low-carbohydrate diet (48) and physical activity (49) interventions improve the most prevalent MetS components, especially MetS Z-score (Zmets). Because the measures of interaction on the additive scale revealed that the combined effects of exercise and KD on Zmets were more than the sum of the individual effects, current results support their synergistic effect and importance for the control of MetS conditions.…”
Section: Discussionsupporting
confidence: 92%